Fishing Gear Research at the Central Institute of Fisheries Technology - Kuriyan, G. K. (Fishery Technology, 1968)
Ever since the advent of Independence, the central objective of public policy and the nation’s endeavour have been the promotion of a rapid and balanced economic development. Hardly anywhere does this apply more distinctly than in the field of marine fishing, where a remarkable degree of mechanisation has already been registered for a greater and more efficient exploitation of the existing resources. The Craft and Gear Wing of the Central Institute of Fisheries Technology was, therefore, established to develop the country’s fishing boats and implements scientifically and systematically. The Wing was organised in the year 1957 as a part of the fisheries development schemes included under the Second Five Year Plan. Although initially the development was accelerated, the complexity of modern technology, the inter—action of science and technology resulting in the emergence of new techniques, the demand for more complicated and sophisticated testing equipments and the need for a large number of well trained personnel have all apparently retarded the progress in later years.